GPR119 - a major Enteroendocrine Sensor of Dietary Triglyceride Metabolites Co-acting in Synergy with FFA1 (GPR40) - Ekberg, Jeppe P. (Endocrinology, 2016)
Triglycerides are among the most efficacious stimulators of incretin secretion; however the relative importance of FFA1 (GPR40), FFA4 (GPR120) and GPR119 which all recognize triglyceride metabolites, LCFA and 2-MAG respectively, is still unclear. Here, we find all three receptors to be highly expressed and highly enriched in FACS-purified GLP-1 and GIP cells isolated from transgenic reporter mice. In vivo, the triglyceride-induced increase in plasma GIP was significantly reduced in FFA1 deficient mice (to 34% - mean of four experiments each with 8-10 animals), in GPR119 deficient mice (to 24 %) and in FFA1/FFA4 double deficient mice (to 15%) but not in FFA4 deficient mice. The triglyceride-induced increase in plasma GLP-1 was only significantly reduced in the GPR119 deficient and the FFA1/FFA4 double deficient mice, but not in the FFA1 and FFA4 deficient mice. In mouse colonic crypt cultures the synthetic FFA1 agonists, TAK-875 stimulated GLP-1 secretion to a similar extent as the prototype GLP-1 secretagogue neuromedin C, this however only corresponded to approx. half the maximal efficiency of the GPR119 agonist AR231453 whereas the GPR120 agonist Metabolix-209 had no effect. Importantly, when the FFA1 agonist was administered on top of appropriately low doses of the GPR119 agonist a clear synergistic, i.e. more than additive effect was observed. It is concluded that the 2-MAG receptor GPR119 is at least as important as the LCFA receptor FFA1 in mediating the triglyceride-induced secretion of incretins and that the two receptors act in synergy whereas FFA4 plays a minor if any role.